2013
DOI: 10.1116/1.4794383
|View full text |Cite
|
Sign up to set email alerts
|

MBE growth of ZnCdSe/ZnCdMgSe quantum-well infrared photodetectors

Abstract: Articles you may be interested inNear infrared intersubband absorption of CdSe/MgSe quantum wells grown on InP substrate with an InAlAs buffer layer J. Vac. Sci. Technol. B 32, 02C105 (2014); 10.1116/1.4863496 Metastable CdSe/MgSe quantum wells prepared by MBE with near IR intersubband absorption Molecular-beam epitaxy growth and nitrogen doping of hexagonal ZnSe and ZnCdSe/ZnSe quantum well structures on hexagonal ZnMgSSe bulk substratesThe authors report the growth of quantum well infrared photodetectors (QW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Recently, we have shown that selenide-based wide band gap II-VI semiconductors are attractive alternatives for intersubband (ISB) devices, especially those working in the short wavelength range [13][14][15][16]. We have demonstrated that QWIPs with high performance can also be fabricated from ZnCdSe/ZnCdMgSe multiple quantum wells (MQWs) [17][18][19]. ZnCdMgSe can be grown lattice-matched on InP substrates with a large tuneable band gap (from 2.1 to 3.5 eV).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, we have shown that selenide-based wide band gap II-VI semiconductors are attractive alternatives for intersubband (ISB) devices, especially those working in the short wavelength range [13][14][15][16]. We have demonstrated that QWIPs with high performance can also be fabricated from ZnCdSe/ZnCdMgSe multiple quantum wells (MQWs) [17][18][19]. ZnCdMgSe can be grown lattice-matched on InP substrates with a large tuneable band gap (from 2.1 to 3.5 eV).…”
Section: Introductionmentioning
confidence: 97%
“…ISB devices are unipolar devices, in which electron (or hole) transitions happen between energy subbands within the conduction (or valence) band and only one kind of conduction carriers are needed. Since the observation of ISB transitions in semiconductor quantum wells (QWs) [3], various ISB devices such as quantum cascade lasers [4][5][6], quantum-well infrared photodetectors [7][8][9][10][11], and all-optical switches [12,13] have been fabricated. The mature technology for achieving high n-type doping in ZnO makes it possible to employ ZnO-based heterostructures in ISB devices.…”
Section: Introductionmentioning
confidence: 99%